2011
DOI: 10.1007/s10551-011-1195-0
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance as Part of the Strategic Process: Rethinking the Role of the Board

Abstract: Managers are most likely to turn to the board of directors for guidance during a period of crisis. But can good corporate governance prevent an organization from reaching that critical point in the first place? In light of the recent global financial crisis, this question has become all the more pressing, and so to prevent future crises, we argue that corporate boards of directors need to be keenly aware of the potential social harms that might arise from the value-creating activities of the firm they are task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
0
9
0
4
Order By: Relevance
“…Statutory reforms and codes of practice, introduced in response to corporate failures and the behaviours of recalcitrant directors and boards, appear to have done little to improve the quality of corporate governance or company performance either (Leblanc, 2010;Pozen, 2010). Indeed, the agency-based corporate governance system suggests the sharp focus on monitoring and control (Lockhart, 2014a) may have played a significant role (Weitzner and Peridis, 2011) in some failures.…”
Section: The Separation Of Governance and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Statutory reforms and codes of practice, introduced in response to corporate failures and the behaviours of recalcitrant directors and boards, appear to have done little to improve the quality of corporate governance or company performance either (Leblanc, 2010;Pozen, 2010). Indeed, the agency-based corporate governance system suggests the sharp focus on monitoring and control (Lockhart, 2014a) may have played a significant role (Weitzner and Peridis, 2011) in some failures.…”
Section: The Separation Of Governance and Managementmentioning
confidence: 99%
“…Despite two or more decades of scholarly enquiry and debate, no agreement is apparent in the literature as to the appropriate level, scope or nature of the board's involvement in strategy and the strategic management process, or how the board's involvement should be initiated or fulfilled (Hendry and Kiel, 2004). Notwithstanding this, several researchers have suggested that boards should be actively engaged in the strategy selection and decision-making process with management (Andrews, 1980;Bukhvalov and Bukhvalova, 2011) especially during periods of crisis or change (Weitzner and Peridis, 2011) because boards are ultimately responsible for company performance (Bainbridge, 2002) and value creation (Pugliese et al, 2009), and they appear to do this by way of corporate governance. Also, companies with active boards have long been claimed to perform better than those with more passive boards (Wheelen and Hunger, 2006), particularly when effective dynamics exist between the board and management (Barroso et al, 2009).…”
Section: Strategic Decision Making and Performancementioning
confidence: 99%
“…Process and structure are mechanisms or technical aspects needed to control and coordinate various running the company's business. In more detail, the process will regulate the participants' series of actions, while the structure will determine how participants relate to other participants (Weitzner & Peridis, 2011).…”
Section: Good Corporate Governancementioning
confidence: 99%
“…The concept of inclusivity with external stakeholders to the organisation originated from stakeholder theory and indicated that nonprofit boards should make a concerted effort to work towards the best interests of their key external stakeholders (Brown, 2002;Weitzner & Peridis, 2011). Brown (2002) states that a lack of inclusivity can result in the board misinterpreting the needs of their constituents and can result in the implementation of irrelevant organisational policies.…”
Section: Stakeholder Theorymentioning
confidence: 99%